Tax law, state-building and the constitution - De Cogan, Dominic (Oxford [England] : Hart, 2020)
"This monograph looks at how tax is intertwined with constitutional law and the state in the UK's history. It looks at a variety of topics including tax devolution, scrutiny and reform of tax legislation, the protection of taxpayers and the domestic legal processing of international rules and problems. Tax Law, State-Building and the Constitution presents and interrogates five key claims. First, there is a clear overlap between the concerns of tax and constitutional lawyers. Secondly, the tax system is being deeply affected by the fast pace of constitutional change. Thirdly, decisions taken in the tax field are likely to have a reverse influence on the evolution of the constitution. Fourthly, these relationships are heavily context-dependent, with tax making all the difference to some ongoing constitutional controversies whilst having very little to do with others. Fifthly, by acknowledging tax as an important moving part within the contemporary constitution we might understand both tax and constitutional law a little better. The book therefore contributes to deeper theoretical debates on the identity of tax law as a discipline, the relevance of tax to public lawyers, the meaning of state-building in the recent history of a developed country and the importance of the public finances to a wider sense of 'what is going on'. These are questions that ought to command the attention of tax and constitutional law academics as well as policy makers and reformers"--
Tax Law, State-building and the Constitution -- Tax Devolution -- Reform and Scrutiny of Tax Policymaking -- Taxpayer Protection -- Europe and Beyond -- Constitutional Disruption.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Taxation -- Law and legislation -- Great Britain; Constitutional law -- Great Britain; Taxation & duties law; Electronic books